ANALYSIS OF RISK MANAGEMENT IN THE IMPLEMENTATION OF ENTERPRISE RESOURCE PLANNING (ERP) USING THE FMEA METHOD AT PT XYZ: ANALISIS MANAJEMEN RISIKO DALAM PENERAPAN ENTERPRISE RESOURCE PLANNING (ERP) DENGAN METODE FMEA PADA PT XYZ - Santosa, Dewi Shafitri Rachmadhani Putri; Palupi, Ghea Sekar (Journal of Emerging Information Systems and Business Intelligence (JEISBI), 2024)
The fast and complex dynamics of modern business demand effective risk management strategies to support the successful implementation of technology. This research examines the use of Failure Mode and Effect Analysis (FMEA) in risk management during the implementation of Enterprise Resource Planning (ERP) at PT XYZ, a health equipment company in Surabaya. The aim of this research is to identify potential operational risks and formulate strategic recommendations to mitigate these risks effectively. This research method includes qualitative analysis based on in-depth interviews and evaluation of related documentation. The research results identified various risks with different categories, namely high, medium and low risks, each of which requires certain mitigation steps. This research found that the integration of FMEA and ISO 31000:2018 was able to strengthen the risk identification, evaluation and management process in a systematic and structured manner. This research confirms that ERP systems, although important for the integration and automation of business processes, still contain significant risks that require a careful management approach. This research contributes to the literature on risk management in ERP implementation and proposes a comprehensive risk management framework to optimize organizational efficiency and reduce the potential for failure. Recommendations for continued research and industry practice are presented, with a focus on ongoing risk evaluation and adaptation of effective risk management frameworks.